Pengembangan Instrumen Asesmen Diagnostik Untuk Mengukur Level Literasi Baca Tulis Peserta Didik Sekolah Dasar - Sutiyono, Sutiyono; Nasrulloh, Rifqi Syarif; Yazidatul, Eisya Syifa; Agustiani, Dwi Irma (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study aims to develop an assessment instrument to measure the reading and writing literacy levels of primary school students. The research method uses R&D with the 4D model but is limited to the define, design and develop (3D) levels. The research subjects were limited to one class in each school including SD IT Salsabila Klaseman Yogyakarta, SD Teladan Yogyakarta, SD N Timbulharjo Yogyakarta, SD IT Sunan Averoes Yogyakarta, and SD NU Sleman Yogyakarta. Data collection techniques through validation tests by expert judgment, namely language experts, educational evaluation experts, and experts in the field of basic education. The results showed that it was in the very feasible category based on the validation test with an average percentage of 95%. The results of the limited trial of the literacy diagnostic assessment instrument pointed to a very feasible category. By exceeding the specified standards, it indicates that the diagnostic assessment of students' literacy is considered qualified and very feasible to be used as a learning resource for elementary school students.